Breast-feeding and early childhood caries: an assessment among Brazilian infants - A. ROSENBLATT, & P. ZARZAR (Paediatric Dentistry, 2004)
The purpose of the present study was to evaluate early childhood caries among 12–36-month-old children from families living in poor socio-economic conditions in the city of Recife, Brazil, its association with the type and duration of feeding (e.g. natural, sugared, bottle and glass), as well as the relationship between a supplementary diet and the occurrence of this type of caries.